Analysis of the prevalence, intensity and features of the clinical course of caries in early childhood and preschool children based on the data of preventive medical examinations - O. M. Davidian; A. V. Fomina; E. A. Lukyanova; E. M. Shimkevich; D. A. Nazarova; A. P. Kotelnikova; E. S. Shilyaeva (Эндодонтия Today, 2021)
Aim. To study the prevalence, intensity and features of the clinical course of caries in children from 1 to 5 years old, to improve the registration of dental morbidity.Materials and methods. An epidemiological and clinical examination of the child population was carried out as part of preventive medical examinations of minors. The study involved 1930 children from Moscow, aged from 1 to 5 years. The epidemiological survey was carried out to study the dental morbidity in children of early childhood and preschool age. Clinical research methods were carried out to determine the dental status of the subjects. All studies in children were performed with informed voluntary consent. Parents or legal representatives signed their consent to the survey. Results. Analysis of the results of preventive medical examinations of minors made it possible to determine the prevalence, intensity and characteristics of the clinical course of caries in the period of early childhood (preschool period) and preschool age among the children's population of Moscow.Conclusions. It was found that the prevalence and intensity indicators increase as children grow up, the depth of the lesion and the localization of carious lesions change at different age periods.